Efficient lithium-ion storage using a heterostructured porous carbon framework and its in situ transmission electron microscopy study. Issue 6 (22nd December 2021) - Kim, Minjun; Fernando, Joseph F. S.; Wang, Jie; Nanjundan, Ashok Kumar; Na, Jongbeom; Hossain, Md. Shahriar A.; Nara, Hiroki; Martin, Darren; Sugahara, Yoshiyuki; Golberg, Dmitri; Yamauchi, Yusuke
Abstract : The unique 3D heterostructure can highly tolerate the volume expansion over repetitive charge/discharge of lithium-ion batteries, which has been demonstrated through in situ transmission electron microscopy. Abstract : A heterostructured porous carbon framework (PCF) composed of reduced graphene oxide (rGO) nanosheets and metal organic framework (MOF)-derived microporous carbon is prepared to investigate its potential use in a lithium-ion battery. As an anode material, the PCF exhibits efficient lithium-ion storage performance with a high reversible specific capacity (771 mA h g −1 at 50 mA g −1 ), an excellent rate capability (448 mA h g −1 at 1000 mA g −1 ), and a long lifespan (75% retention after 400 cycles). The in situ transmission electron microscopy (TEM) study demonstrates that its unique three-dimensional (3D) heterostructure can largely tolerate the volume expansion. We envisage that this work may offer a deeper understanding of the importance of tailored design of anode materials for future lithium-ion batteries.